Neighbourhood deprivation, life satisfaction and earnings: Comparative analyses of neighbourhood effects at bespoke scales - Gundi Knies; Patricia C. Melo; Min Zhang (University of Essex, Institute for Social and Economic Research (ISER), 2020)
We investigate the effect of neighbourhood deprivation on individual subjective and objective wellbeing for England and Wales. Our identification strategy combines rich longitudinal information on individual characteristics, family background and initial job conditions with panel data estimators and sample restrictions, which address residential sorting bias and neighbourhood-specific confounding effects. Our findings suggest that the effect of neighbourhood deprivation on life satisfaction and wages is not a genuine causal effect, but largely explained by strong spatial sorting mechanisms. We also find that the results overall do not vary by the bespoke spatial scale used to operationalize neighbourhoods.
Keywords: I31; C23; D31; I30; 330; neighbourhood effects; life satisfaction; wages; bespoke neighbourhoods